A SOFT SYSTEMS METHODOLOGY APPROACH TO IMPROVING THE SUPPLY CHAIN OF A CONSTRUCTION PROJECT IN GAUTENG PROVINCE, SOUTH AFRICA - Lewis Tsuro; Stan Hardman (Journal of Construction Project Management and Innovation)
The Soft Systems Methodology (SSM) was developed as a set of tools for identifying and making incremental steps to improve situations with poorly defined causes or solutions. The supply chain forms a key process of any construction project; however, on any given construction site, supply chain inefficiencies could arise from many different avenues. Opinions vary, though, on which of these avenues is more important for increasing supply chain efficiencies; whether any problem even exists across the different aspects of the supply chain; as well as what steps should be taken to resolve them. It was therefore studied, here, whether SSM could be employed as a useful tool to systematically apply in the supply chains of a construction project in South Africa, for understanding and targeting the problematic situations that arise. Following thorough cyclical open-ended interviews with 17 workers, supervisors, foremen, site clerks, senior managers, and the CEO of the principal contractor at a new office park construction project in Rosebank, Johannesburg, and a thematic analysis of the data, SSM was performed to understand the existing challenges and develop a suitable model for improvement. The study found that SSM was a good tool for understanding the ‘messy’ circumstances surrounding the chosen construction project supply chain, as well as actions that could be taken to improve the supply chain’s efficiency on site. The findings add weight to the argument that SSM could be a good tool for project managers to systematically introduce into their project planning regimens.